THE LOCAL GOVERNMENT POLICY IN BORDER AREA ON THE EDUCATION RIGHTS FULFILMENT FOR PERSON WITH DISABILITIES IN NORTH KALIMANTAN PROVINCE - Yahya Ahmad Zein; Arif Rohman; Dewi Nurvianti (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
The research problems are; first, how is local government authority within human rights fulfilment for person with disabilities? Second, how is legal policy on human rights for person with disabilities?. Third, how is law protection from local government related to education rights fulfiment for person with disabilities in North Kalimantan?. The method of this research uses normative method be equipped by field research. This research is important considering the obligation of state to protect, to recognize and to fulfil of human rights for citizens in its region without discrimination particulary for person with disabilities in border area. Within an effort to implementation, Indonesia Government regulates some legal instrument of human rights, one of the newest is Law No 8 of 2016 on Person with Disabilities. North Kalimantan is youngest province in Indonesia, some local regulation on human rights has been regulated, but the human rights instrument particulary for person with disabilities has not been set up. The research urgency becomes one of the goals to regulate the local government policy on education rights particularly the rights of person with disabilities in North Kalimantan Province, its expected to be a solution against regulation plan in Indonesia on fulfilment of human rights degree for person with disabilities especially education rights for them in North Kalimantan Province. The methodology of this paper is normative that equipped by field research. The conclussion of this paper is in regulation, authority, and legal protection.